If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5z-7=6z-6
We simplify the equation to the form, which is simple to understand
5z-7=6z-6
We move all terms containing z to the left and all other terms to the right.
+5z-6z=-6+7
We simplify left and right side of the equation.
-1z=+1
We divide both sides of the equation by -1 to get z.
z=-1
| 9+1/9= | | 35x^2+47x+6=0 | | 40=80u | | sin(t^3)=2(t^3) | | (4+4i)(-4+4i)= | | -4m+8=20 | | 18=2x-4(-4x+18) | | 1r+t-8r+13t= | | 4(5z+1)-7=157 | | 3+6(1-6x)= | | (6x)3=2+8 | | 4/7x=x/7 | | 2sin(4x-1)=1 | | 66=31-5(x-4) | | y=-1/3x-7 | | 8=s-14 | | -21=6+3v | | 3x-8x+x-5x= | | 5+2p=37 | | 2+3=x-8 | | 2x^4-200=0 | | 320=150x+d | | math=48 | | 21x(2)=8x+6 | | 2.4b+5.6=-11.3 | | (3d-19)+6d=53 | | 43=4 | | 4x-3y=185 | | 9+1/9=0 | | 2.4b+5.6= | | 3x+16-2x=7+3x-5 | | 27x/-4 |